Broad Thumbs and Toes with Mental Retardation; Syndrome of Rubinstein and Taybi - Purnomo Subagiyo; J. S. Bliek (Indonesian Pediatric Society, 1974)
Seeing the unusual syndrome inan Indonesian baby we consideredpublication worthwhile.The Rubinstein and Taybi syndro-me consists of a large number ofcongenital anomalies. Some of theseare common to all cases, many areseen in some cases only.